New Records of a dangerus invasive pests − Brown marmorated stink bug Halyomorpha halys Stal, 1855 (Heteroptera, Pentatomidae) in Kazakhstan - I. I. Temreshev; P. A. Esenbekova; A, M. Uspanov (Acta Biologica Sibirica, 2018)
Brown marmorated stink bug Halyomorpha halys was first found in Kazakhstan in 2016. It is a dangerous invasive pest of agriculture. In Almaty and the Almaty oblast in 2017-2018, new finds of the Brown marmorated stink bug were made, which indicates the existence of its stable population in this region and the gradual expansion of the range of the species. A calendar of phenology of pest development in the southeast of Kazakhstan was compiled. Eating of egg-laying of Brown marmorated stink bug by ladybirds Propylea quatuordecimpunctata (Linnaeus, 1758) and Harmonia axyridis (Pallas, 1773) was noted.